Towards Metric Temporal Answer Set Programming. Issue 5 (September 2020) - CABALAR, PEDRO; DIÉGUEZ, MARTÍN; SCHAUB, TORSTEN; SCHUHMANN, ANNA
Abstract: We elaborate upon the theoretical foundations of a metric temporal extension of Answer Set Programming. In analogy to previous extensions of ASP with constructs from Linear Temporal and Dynamic Logic, we accomplish this in the setting of the logic of Here-and-There and its non-monotonic extension, called Equilibrium Logic. More precisely, we develop our logic on the same semantic underpinnings as its predecessors and thus use a simple time domain of bounded time steps. This allows us to compare all variants in a uniform framework and ultimately combine them in a common implementation.